The Isle of the Lost : a Descendants novel / 1. - De la Cruz, Melissa, 1971- (Descendants (Disney Hyperion Books), 2015)
Imprisoned on the Isle of the Lost, the teenaged children of Disney's most evil villains search for a dragon's eye--the key to true darkness and the villains' only hope of escape.